Raising the Impact of Education Research in Africa - Wolhuter, Charl (AOSIS, 2018)
The low demonstrable effect of education research done in South Africa in particular - and Africa in general - continues to be a problem in scientific records in the educational sciences. This scholarly collected work addresses this obstacle and focuses on recommendations from scholars in different sectorial categories in the field of education. Scholars from a variety of sub-fields within the educational sciences reflect on this particular matter, revisiting the history of research and research outcomes and offering informed recommendations based on in-depth investigation and analysis of aspects of the various discourses within the relevant sub-fields. The scope of the content of this collected work centres on the issue of the lack of scientific records concerning the scientific raising of the impact of education research. The book aims at making a specific contribution to the educational sciences by stimulating scholarly discussion around how to increase the recording of the significance of educational research done in Africa, and in South Africa in particular, and to redirect the research agenda into the direction of making more impact. Impact is conceptualised to mean both scholarly impact (that is being cited and being used as foundation for theory building and for further research) and practical impact (that is improvement of practice, teaching and learning in education institutions at all levels).